Variations in the performance, fruit shelf life, and mineral compositions of two varieties of pepper (Capsicum chinense ) grown under different soil amendments and seasons - Christopher Aboyeji; Aruna Adekiya; John Afolayan; Faith Okunlola; Barnabas Akaazua; Nifemi Adesola (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: A study was carried out during the 2021 dry season and 2022 rainy season to evaluate the differences in the performance, fruit longevity, mineral, and vitamin C compositions of two varieties of pepper (Capsicum chinense) cultivated using different organic amendments and inorganic fertilizer as a check. Poultry manure (PM), Tithonia diversifolia (TD), cattle manure (CM), inorganic fertilizer (NPK 15:15:15), and the control (CTRL) were used as treatments.Method: Organic amendments were applied at a rate of 20 t ha-1, while NPK was applied at a rate of 180 kg ha-1. The experiment was a 2 x 2 x 5 factorial with three replications laid out in a Randomised Complete Block Design. Vegetative, yield, and quality parameters were collected.Results: Results show that Caribbean red produced higher values for vegetative parameters, yield, and longer shelf life in season 1. In a similar vein, mineral compositions (Cu, Ca, and Mg) of the Caribbean red variety were found to be higher than that of the Efia variety. Results also indicated that the use of poultry manure was found to improve the vegetative parameters, increased the number of days to fruit shrinkage, and increased the Ca, Cu, Mg, and vitamin C content. Conclusion: This study, therefore, concludes that the use of the Caribbean red variety cultivated during the dry season (season 1) under the application of poultry manure will give the best vegetative performance, longer shelf life, and improved fruit minerals and vitamin C contents.